Determination of Phenolics and Antioxidant Properties in Tea and the Effects of Polyphenols on Alpha-Amylase Activity - Nadiah, N.I.; Cheng, L.H.; Azhar, M.E.; Karim, A.A.; Uthumporn, U.; Ruri, A.S. (Pakistan Journal of Nutrition, 2015)
Total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity on different type of tea (green, black and oolong) which were extracted by using three types of solution (ethanol, methanol and water) were analyzed. Ethanol extraction obtained the highest total phenolic content, followed by methanol and water. Green tea obtained the highest TPC, TFC and antioxidant activity followed by oolong and black tea. Gallic acid, caffeine and four catechins (catechin, gallocatechin, epicatechin and epigallocatechin) were analyzed and quantified by using High Performance Liquid Chromatography (HPLC). The effects of addition of tea extracts on starch hydrolysis by using alpha-amylase (37°C) were studied. The extent of starch hydrolysis (with addition of tea extracts) followed the order: green>oolong>black tea. The lowest degree of hydrolysis for black tea was evident from the highest inhibitory of black tea on the activity of alpha-amylase.